Mediating Role of Oil Production in Non-Tax State Revenue Determinants - Wahyu Suryo Majid; Mohammad Raung Yuniar Effendy (Universitas Negeri Semarang, 2025)
This study aims to analyze the effect of the Indonesian Crude Price (ICP) and upstream oil and gas state-owned assets on oil non-tax state revenue from the oil and gas sector, with oil production considered as a potential mediating variable. Using the Vector Autoregression (VAR) model, the study examines short-run relationships through Granger causality and t-statistics, as well as long-term contributions via Forecast Error Variance Decomposition (FEVD). The results show that the ICP has a positive and statistically significant effect on oil non-tax state revenue. In contrast, upstream oil and gas state-owned assets and oil production do not exhibit significant short-run effects. Moreover, oil production does not function as a mediator in the relationship. Nonetheless, FEVD results suggest that the ICP and oil production make meaningful long-term contributions to oil non-tax state revenue, indicating underlying structural links not captured by short-run causality. These findings highlight the importance of managing oil price fluctuations and designing fiscal structures that are responsive to global oil market dynamics.